Effects of Crystallite Sizes of Pt/HZSM-5 Zeolite Catalysts on the Hydrodeoxygenation of Guaiacol - Haonan Duan; Yajie Tian; Siyuan Gong; Bofeng Zhang; Zongjing Lu; Yinqiang Xia; Yawei Shi; Congzhen Qiao (Nanomaterials, 2020)
Herein, Pt/HZSM-5 zeolite catalysts with different crystallite sizes ranging from nanosheet (~2 nm) to bulk crystals (~1.5 μm) have been prepared for the hydrodeoxygenation of guaiacol, and their effects on the reaction pathway and product selectivity were explored. HZSM-5 zeolites prepared by seeding (Pt/Z-40: ~40 nm) or templating (Pt/NS-2: ~2 nm) fabricated intra-crystalline mesopores and thus enhanced the reaction rate by promoting the diffusion of various molecules, especially the bulky ones such as guaiacol and 2-methoxycyclohexanol, leading to a higher cyclohexane selectivity of up to 80 wt % (both for Pt/Z-40 and Pt/NS-2) compared to 70 wt % for bulky HZSM-5 (Pt/CZ: ~1.5 μm) at 250 °C and 120 min. Furthermore, decreased crystallite sizes more effectively promoted the dispersion of Pt particles than bulky HZSM-5 (Pt/Z-400: ~400 nm and Pt/CZ). The relatively low distance between Pt and acidic sites on the Pt/Z-40 catalyst enhanced the metal/support interaction and induced the reaction between the guaiacol molecules adsorbed on the acidic sites and the metal-activated hydrogen species, which was found more favorable for deoxygenation than for hydrogenation of oxygen-containing molecules. In addition, Pt/NS-2 catalyst with a highly exposed surface facilitated more diverse reaction pathways such as alkyl transfer and isomerization.